PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 001 SEIKIJANG KECAMATAN BANDAR SEIKIJANG - Yeni Marleni; Munjiatun Munjiatun; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem of the research is the low of the result of the students’ science study with average 46,67. Contextual Teaching and Learning Model gives the opportunity to students to improve the result of the science study of fourth grade students of SDN 001 Seikijang. The subject of the research is the fourth grade students of SDN 001 Seikijang of 2014 academic year. They are 30 students. The research is a Class Action Research which is done in two cycles. Each cycle is applied in twice meeting with once examination at the end of cycle. The collecting data instruments on the research are teacher observating paper, student observating paper and the examination of the end of cycle. The research is conducted in class action research, aimed to improve the result of the fourth students in science study learning of SDN 001 Seikijang. The result shows that Contextual Teaching Learning Model can improve the result of the students’ learning in science study. It is shown on the basic score of school average 46,67 with 23,33% classical result then increases in the school avarage 73,16 in the cycle I with 63,33%, classical result and increases 57,76% and on the cycle II the class average improves to 80,17 with 90%classical result, and improves from basic score to daily examination I 71,76%. The increase of the result of the study in supported by the increase of teacher and students activity. The teacher’s activity increases with 60,71% in cycle I to 85,71% in cycle II. The improvement of the first meeting of cycle I to second meeting of cycle II is 25%. It means that the learning result of fourth students’ in science study of SDN 001 Seikijang.Key words: Contextual Teaching and Learning (CTL), the result of science study.